Domain‐Confined Etching Strategy to Regulate Defective Sites in Carbon for High‐Efficiency Electrocatalytic Oxygen Reduction. (20th January 2022) - Ye, Guanying; Liu, Suqin; Huang, Kui; Wang, Siyuan; Zhao, Kuangmin; Zhu, Weiwei; Su, Yuke; Wang, Jue; He, Zhen
Abstract: Coupling sites of nitrogen dopants and intrinsic carbon defects (N/DC) in metal‐free carbon are highly active toward electrocatalytic oxygen reduction reaction (ORR), and yet they are hard to be effectively constructed. Here, a novel synthesis strategy for fabrication of N/DC‐enriched metal‐free carbon from precursors containing metal‐nitrogen moieties (M‐Nx ) is reported. During pyrolysis of the precursors, the M‐Nx is in situ converted to endogenous metal oxides (MOx ) via a halide‐mediated "bait and switch" mechanism to realize a domain‐confined etching of the carbon matrix around the nitrogen dopants, forming abundant N/DC coupling sites in the final carbon products. The optimized N/DC‐enriched carbon exhibits an outstanding ORR activity and stability with a half‐wave potential of 0.903 V (versus RHE) in 0.1 m KOH solution, outperforming most of the reported metal‐free carbon catalysts. Experimental investigations and theoretical calculations demonstrate an improved electron‐donating ability and optimized binding energies of the N/DC coupling sites toward the ORR intermediates, which are primarily responsible for such an excellent ORR activity. This domain‐confined endogenous MOx etching strategy is also widely applicable to different M‐Nx ‐containing precursors as well as different halide mediators, which opens up new possibilities to fabricate metal/nonmetal doped carbon materials enriched with various coupling sites of desired synergistic properties. Abstract : Coupling sites of nitrogen dopants and intrinsic carbon defects (N/DC) are effectively constructed in metal‐free carbon by domain‐confined etching of endogenous metal oxides that are derived from the M‐Nx moieties in precursors with the mediation of halides. The N/DC‐enriched metal‐free carbon exhibits an excellent ORR catalytic activity. This work sheds light on directional fabrication of synergistic coupling sites in carbon.